The priority of government investment for companies manufacturing sector in Iraq - رشيد, ثائر محمود; مظلوم, مهج صالح (Journal of Economics and Administrative Sciences, 2018)
The study aimed at clarifying the contradictions of the general industrial companies despite the investment allocations and the government investment expenditure on manufacturing activities under the so- called rehabilitation programs. However, this did not contribute to a certain extent in the growth and industrial leap in the direction of developing the activities of the sector Industrial sector in Iraq because of the lack of adoption of a number of basic principles towards the need to take priority of investment in the field of manufacturing and industrial decision-making in the restructuring of industry according to the priorities of investment in light of the international industrial trend, Tosmarah available to the manufacturing industry and the selection of those companies that can achieve successful investments and ensure the restructuring of general industrial companies. As well as the presentation and explanation of the legislative and institutional frameworks that facilitate the process of industrial investment and the definition of industrial capabilities and the possibilities of cooperation with the private sector through various mechanisms and methods to adapt to the reality of the competitive advantages of industrial companies globally, including the ability to meet domestic demand, to develop production processes and workers and improve product quality and systems Working and securing the legal and banking environment for companies, including the development of industrial policy legislation that protects the national product to avoid external pressures.